Gastrocnemius muscle flap for coverage of knee defects in the injuries of popliteal artery: a clinical case report - Zarch, Mohammadali Babaei; Mahmoudi, Samira; Shirazi, Mohammad Hadi Gerami; Fereidouni, Armin (Frontiers in Surgery, 2024)
The use of the gastrocnemius muscle flap has become an excellent choice for coverage of Knee Defects. However, the surgical management of gastrocnemius muscle flap in the injuries of the popliteal artery remains a challenging therapeutic problem. The purpose of this manuscript is to present a case of a successful knee gastrocnemius flap in a patient with popliteal artery injuries. In 2024, a 46-year-old woman with a tibia fracture and popliteal artery injury went to the emergency department of Namazi Hospital. In the first step, the external fixator of the tibia bone was performed to fix the fracture. Then, popliteal artery anastomosis was performed. After two weeks, all internal implants were removed due to abscess. Four weeks later, the patient's skin developed necrosis and was repaired using medial hemi gastrocnemius Muscle flaps. We present a case of the successful use of medial hemi gastrocnemius Muscle flaps for Coverage of knee defects in the injuries of the popliteal artery.